Changes in cardiac function following a speed ascent to the top of Europe at 4808 m - Champigneulle, B.; Doutreleau, S.; Baillieul, S.; Brugniaux, J. V.; Robach, P.; Bouzat, P.; Verges, S. (European Journal of Applied Physiology, 2022)
Purpose Both prolonged exercise and acute high-altitude exposure are known to induce cardiac changes. We sought to describe the cardiac responses to speed climbing at high-altitude, including left ventricular (LV) performance assessment using the myocardial work index (MWI), a new index derived from 2D speckle tracking echocardiography (STE).